AKTIVITAS ANTIOKSIDASI DAN PENILAIAN ORGANOLEPTIK SOSIS DAGING SAPI DAN SUSU PASTEURISASI YANG DIBERI PEWARNA PIGMEN EKSTRAK KULIT BUAH NAGA (Hylocereus spp) - Sopandi, Tatang; Wardah, Wardah (Universitas PGRI Adi Buana Surabaya, 2010)
An experimental research has been carried out to investigate the antioxidant activity of pigment from the extract of peel dragon fruits (Hylocereus spp) and the effect of various concentration of extract of peel dragon fruit as a colorant on sensory characteristic of beef sausage and milk pasteurization. Antioxidant activity of pigment from peel of dragon fruit extract in beef sausage were used by thiobarbituric acid test (TBA) in 1, 2, 3, 4, 5, 6 arid 7 days. Eight trained panelist have 0.1% sugar threshold was judged color and taste of milk pasteurization and beef sausages. The result show that the pigment of peel dragon fruit inhibited oxidant activity in beef sausage. Panelists significant prefer color and taste beef sausage and milk pasteurization that treated by pigment extract of peel dragon fruit.